Lifetime Estimation Complementing Reliability Testing of Electronic Devices - Kenttä, Caijus (My University, 2016)
The key factor for competitiveness, in all industrial sectors, is to continuously enhance the quality of the products and the productivity. There are numerous ways to improve product quality, but necessary no one correct way to implement tasks that are needed. But in the essence of product quality is understanding the field conditions that the product will meet, and base the product testing accordingly. The internal testing methodology in Danfoss Vaasa site has been systematically devel-oped from the very beginning of Vacon frequency converter manufacturing and has been successfully implemented for many years. Still there is always room for improve-ment on testing productivity. Long time the development of reliability testing methods has lean heavily on product and component testing and not direction of models and mathematical methods. However, it is possible to complement testing and improve its productivity with various mathematical models and methods. This thesis first presents the basics on different environmental conditions and stressor that will affect electronic devices. Secondly, the test methods and standards that are commonly used for environmental testing. These foundations needs to be established to understand the models that are used to express the accelerating effects to product life-time and typical mathematical methods that are then used for lifetime estimations based on the data obtained from tests. On the basis of these, this thesis present suggestions on how to use these methods to enhance the productivity of testing processes for new products are developed and for products that are in active production. Also test case is presented on how to use life data analysis to improve productivity of testing is presented. In the case study, test data from accelerated lifetime test is examined to reveal potential reduction of overall test time and possible also inaccurate lifetime estimation made by the component supplier.
Keywords: Reliability; Accelerated life testing; Life data analysis; fi=Sähkötekniikka|en=Electrical Engineering|; fi=Sähkö- ja energiatekniikan koulutusohjelma (DI)|